Worker Absenteeism in Search Equilibrium - Per Engström; Bertil Holmlund (Uppsala University, Department of Economics, 2005)
The paper presents a tractable general equilibrium model of search unemployment that incorporates absence from work as a distinct labor force state. Absenteeism is driven by random shocks to the value of leisure that are private information to the workers. Firms offer wages, and possibly sick pay, so as to maximize expected profits, recognizing that the compensation package affects the queue of job applicants and possibly the absence rate as well. Shocks to the value of leisure among nonemployed individuals interact with their search decisions and trigger movements into and out of the labor force. The analysis provides a number of results concerning the impact of social insurance benefits and other determinants of workers and firms behavior. For example, higher nonemployment benefits are shown to increase absenteeism among employed workers. The normative anlysis identifies externalities associated with firm-provided sick pay and examines the welfare implications of alternative policies. Conditions are given under which welfare equivalence holds between publicly provided and firm-provided sick pay. Benefit differentiation across states of non-work are found to be associated with non-trival welfare gains.
urn:nbn:se:uu:diva-211066
Keywords: J21; J64; J65; 330; Absenteeism; search; unemployment; social insurance; Fehlzeit; Friktionelle Arbeitslosigkeit; Sozialversicherung; Lohnfortzahlung; Zeitverwendung; Personalzusatzkosten; Leistungsmotivation; Arbeitsangebot